Problem with output relays used in microprocessor-based protection devices: what to do? - Gurevich, V.I. (Електротехніка і електромеханіка, 2007)
It is the author’s second publication on nonconformance of parameters of subminiature output relays used in microprocessor-based protective devices to actual operation conditions and standards. The article suggests adjustment of the standards and presents specific engineering solutions to this problem. Друга публікація автора на тему про невідповідність параметрів субмініатюрних вихідних реле мікропроцесорних пристроїв релейного захисту реальним умовам експлуатації і стандартам, що діють. У даній статті пропонуються заходи по уточненню стандартів, а також приводяться конкретні технічні рішення цієї проблеми. Вторая публикация автора на тему о несоответствии параметров субминиатюрных выходных реле микропроцессорных устройств релейной защиты реальным условиям эксплуатации и действующим стандартам. В данной статье предлагаются меры по уточнению стандартов, а также приводятся конкретные технические решения этой проблемы.